Flipped Learning Instruction and Pragmatic Competence: A Case of English for Accounting Students - Arif Nugroho; Rahima Fitriati (English Learning Innovation (englie), 2021)
Twenty-first century English language teaching is the witness of advanced Information and Communication Technology (ICT). Integrating digital technologies in English teaching activities is a prerequisite to enhance learning efficacy and achieve the goal of English communicative competence. Hence, this study examines the impact of flipped learning instruction on pragmatic competence of a group of English for specific purposes students’, i.e. English for Accounting. This pre-experimental study was conducted in ten meetings by involving 36 English for Accounting students of a public university in Surakarta Indonesia as the participants. Drawing on a Discourse Completion Test (DCT) and Focus Group Discussion (FGD), the results portrayed that there was a significant difference between the results of pre-test and post-test on DCT, meaning that the students’ pragmatic competence significantly improved after participating in the flipped learning instruction. An FGD was further conducted to reveal the students’ attitudes about the practice of flipped learning and the results indicated that they positively perceived the implementation of the teaching model in English for Accounting class. These results contribute to offering fruitful insights for teachers and future researchers about the practice of flipped learning instruction in English language teaching, particularly in the context of English for specific purposes.  Keywords: English for Accounting, Flipped Learning, Pragmatic Competence